AF-React study: Prevalence of thrombotic events in patients with atrial fibrillation receiving NOACs – real-world data analysis from northern Portugal primary healthcare - Pinto, Susana Silva; Teixeira, Andreia; Henriques, Teresa S.; Monteiro, Hugo; Martins, Carlos (Frontiers in Medicine, 2024)
Introduction: Anticoagulation is recommended for stroke prevention in patients with atrial fibrillation (AF). The guidelines suggest non-vitamin K antagonist anticoagulants (NOACs) as the primary therapy for anticoagulation in AF. Several patient-related factors increase the risk of thrombotic events: elderly individuals, a previous history of stroke, and chronic kidney disease. This study aims to determine the association between NOACs and other patient variables in AF and the occurrence of thrombotic events. Methods: The database included all adults with the code K78 (ICPC-2 code for AF) who received clinical care in Northern Portugal’s Primary Health Care between January 2016 and December 2018 and were dispensed the same NOAC at the pharmacy (never changed anticoagulant medication). Results: The results indicate that 10.2% of AF patients on NOAC anticoagulation experienced a stroke. Furthermore, patients treated with apixaban and dabigatran had higher odds of experiencing a stroke compared to those treated with rivaroxaban. Among patients with the same age, gender, and CHA2DS2Vasc Score, apixaban was significantly associated with a higher likelihood of thrombotic events than rivaroxaban. Discussion: Among AF patients on NOAC anticoagulation, 10.2% experienced a stroke. Patients treated with apixaban and dabigatran had higher odds of stroke (statistically significant) than those treated with rivaroxaban and patients of the same age, gender, and CHA2DS2Vasc Score, apixaban was significantly associated with a greater likelihood of experiencing a thrombotic event relative to rivaroxaban. These results have not been previously reported in studies with real-world data; therefore, a more detailed analysis should be conducted to enhance the validity of these findings.